Sosialisasi Edukasi Kesehatan Pasca COVID-19 dan Pembuatan Handsanitizer untuk Kesehatan Masyarakat Di Desa Bantengputih, Karanggeneng, Lamongan - Rosady, Siti Duratun Nasiqiati; Maknunah, Jauharotul; Sari, Eli Novita (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The habit of implementing clean and healthy living behavior is not easy, it requires understanding and motivation from individuals so that each individual is more disciplined in implementing it. The methods used in this service are data collection, making trash cans and providing post-COVID-19 Health Socialization education and making handsanitizers. The population of the white bull village is 1950 people, with the highest level of education being elementary school graduates so that many of the residents are unemployed. Most types of work are private employees/factory workers and farmers. The work programs that we carry out have had a positive influence on the people of Bantengputih Village, because the goals in each work program are very comprehensive in all circles.